Literature Review: Perkembangan Keterampilan Profesi Akuntan - Wallu, Fitriani; Jaya, I Made Laut Mertha; Andrianto, Wahyu; Anan, Edy (Gorontalo Accounting Journal, 2024)
This research was conducted to find out the development, description, and opportunities for accountant professional skills in Indonesia so far. This research uses a qualitative method, with a literature review design. The more advanced the business world, of course, will affect the increasingly complex transactions that occur both in terms of type and in terms of the number of transactions themselves. In the end, this will directly affect the progress of the accounting discipline itself. This research identifies several skills that are necessary and important for the accounting profession in Indonesia, namely technical skills, generic skills, and technology and IT skills. The skill development of the accounting profession in the future has changed a lot compared to the past. They can do digital record keeping, which reduces time, despite the different opportunities in the accountant and auditor careers. Since the implementation of robotic technology is quite large, they still cannot perform all important tasks. Future accountants may also find new jobs and more responsibilities. As a result, accountants need the ability to adjust to technological changes that will continue to occur. Future accountants must have information technology, critical thinking, and problem solving skills.